(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Paullinia pinnata (PP) is a medicinal vine used folklorically as a result of this attribute to treat various ailments. Ethylene glycol monomethyl ether (EGME) is a solvent of wide application and has been shown to be toxic. This study is designed to elucidate the potential of P. pinnata methanol leaf extract in preventing the deleterious effect of EGME in the liver and kidney. As a sequel to our previous study, seventy adult male Wistar rats were weight-matched into seven groups (n=10). Groups I and II served as controls and received distilled water and 10% dimethyl sulfoxide, respectively. Group III received EGME (200 mg/kg) only. Groups IV-VII were co-treated with EGME (200 mg/kg) and PP at 25, 50, 75 and 100 mg/kg doses, respectively. The administration was done by oral gavage daily for 14 consecutive days. On day 15, the animals were euthanized by cervical dislocation and the liver and kidneys were excised. Sections of the liver and kidney were fixed in 10% formalin for histology. The remainder liver and kidney were processed and used for liver function and kidney function assays, respectively. EGME significantly (p<0.05 )increased the activities of alkaline phosphatase, alanine aminotransferase, aspartate aminotransferase, and gamma-glutamyl transferase in the liver, while the concentration of sodium ion was reduced in the kidney. Lesions were observed in the EGME only and EGME + PP (25 mg/kg) groups and not in the other co-administered groups. The methanol leaf extract of Paullinia pinnata prevented the perturbations of EGME at moderate doses in the liver and kidney.